THE AFFIRMATION OF SELF-EXISTENCE IN “LADY OF SCANDAL’’ BY TINA GABRIELL - Tomi Arianto; Noviana Osinta Bere (Asosiasi Ide Bahasa Kepri, 2020)
This study aimed to analyse the affirmation of self-existence against patriarchal construction in the novel